Visual Techniques as a New Teaching Approach For Construction Engineering Course in UTHM - Tay Hui Suan, Eva Natasha; Ismail, Isham bin (Recent Trends in Civil Engineering and Built Environment, 2021)
This study is to provide a new approach in learning and teaching process for BFC 21002 course at the Faculty of Civil Engineering and Built Environment in UTHM. This study was conducted to help lecturers and students to get a better understanding of the concept of the construction process through VR system that meets the requirements of BFC21002 Construction Engineering syllabus. The findings of this study prove that VR systems can help built more interest in learning and teaching process as well as improving student’s prestige in doing a stimulation. The learning process is also easier to understand with the help of virtual reality experience which gives an idea of the real situation of how a building were built. Although the use of VR techniques in the learning and teaching process is still unclear for the future, the average VR system users provide positive feedback about this system for training sessions in helping them to improve their individual performance. In the future, technological assistance in education will be a successful learning and teaching platform in the field of education.